Proportionate universalism in practice? A quasi-experimental study (GoWell) of a UK neighbourhood renewal programme's impact on health inequalities. (March 2016) - Egan, Matt; Kearns, Ade; Katikireddi, Srinivasa V.; Curl, Angela; Lawson, Kenny; Tannahill, Carol
Abstract: Recommendations to reduce health inequalities frequently emphasise improvements to socio-environmental determinants of health. Proponents of 'proportionate universalism' argue that such improvements should be allocated proportionally to population need. We tested whether city-wide investment in urban renewal in Glasgow (UK) was allocated to 'need' and whether this reduced health inequalities. We identified a longitudinal cohort (n = 1006) through data linkage across surveys conducted in 2006 and 2011 in 14 differentially disadvantaged neighbourhoods. Each neighbourhood received renewal investment during that time, allocated on the basis of housing need. We grouped neighbourhoods into those receiving 'higher', 'medium' or 'lower' levels of investment. We compared residents' self-reported physical and mental health between these three groups over time using the SF-12 version 2 instrument. Multiple linear regression adjusted for baseline gender, age, education, household structure, housing tenure, building type, country of birth and clustering. Areas receiving higher investment tended to be most disadvantaged in terms of baseline health, income deprivation and markers of social disadvantage. After five years, mean mental health scores improved in 'higher investment' areas relative to 'lower investment' areas (b = 4.26; 95% CI = 0.29, 8.22; P = 0.036). Similarly, mean physical health scores declined less in high investment compared to low investment areas (b = 3.86; 95% CI = 1.96, 5.76; P < 0.001). Relative improvements for medium investment (compared to lower investment) areas were not statistically significant. Findings suggest that investment in housing-led renewal was allocated according to population need and this led to modest reductions in area-based inequalities in health after five years. Study limitations include a risk of selection bias. This study demonstrates how non-health interventions can, and we believe should, be evaluated to better understand if and how health inequalities can be reduced through strategies of allocating investment in social determinants of health according to need. Highlights: Social interventions such as urban renewal may improve population health. Allocating resources for such interventions according to need may reduce health inequalities. A UK urban renewal programme we examined allocated investment according to need. This appeared to reduce area-level health inequalities.